PKM Implementasi Numerasi pada Pembelajaran bagi Guru MGMP Matematika SMA Kabupaten Semarang - Setyawati, Rina Dwi; Shodiqin, Ali; Pramasdyahsari, Agnita Siska; Endahwuri, Dhian; Agustina, Ferina (Pelita: Jurnal Pengabdian kepada Masyarakat, 2025)
The "Implementation of Numeracy in Mathematics Learning" training was designed for members of the Mathematics MGMP with the aim of strengthening skills in applying numeracy concepts in the learning process. This training introduces various practical methods for integrating numeracy in mathematics learning, including the application of numeracy in the STEM (Science, Technology, Engineering, and Mathematics) curriculum. Technology is also introduced in this training, with the use of software such as Wolfram Mathematica. This software provides sophisticated tools for data visualization and manipulation, which can enrich the mathematics learning experience interactively and deeply (Wolfram, 2020). In addition, this training discusses effective numeracy assessment methods to measure student understanding and progress, such as practical assignments, tests, and constructive feedback (Shute, 2008). During the training, participants discuss challenges and solutions in implementing numeracy, as well as sharing best practices and experiences between participants (Sowder, 2007). Group activities are also carried out to design and test numeracy-based lesson plans, allowing participants to apply the concepts learned in real learning situations (Tharp & Gallimore, 1988). The purpose of this training is to improve the effectiveness of mathematics teaching, support the development of students' numeracy, and facilitate the application of numeracy in daily learning. The Community Partnership Program (PKM) focuses on two main activities: first, providing training to teachers on the application of numeracy in learning, and second, training teachers to design learning tools that integrate numeracy. Thus, this training is expected to optimize mathematics teaching and strengthen students' numeracy skills through an approach based on interactive teaching, technology, and effective assessment.